La Surveillance Prénatale, Au Maroc Cas Des Femmes Ayant Accouché À La Maternité Souissi, CHU (Ibn Sina) Rabat - Housni, Y. El; Boussalwa, E.; Kharbach, A.; Khadmaoui, A. (European Scientific Journal, ESJ, 2016)
The aim of this study is to analyse the prenatal care performed to the women who gave birth at the Souissi Maternity, Ibn Sina University Hospital of Rabat, Morocco. This study is based on a historical cohort with prospective data collection, during the period of 2 April 2013 to 14 April 2013, with 230 patients Hospitalized to deliver. According to the study 96, 5 % of the women interviewed received at least one prenatal consultation from a qualified staff. Despite the high rate of coverage with antenatal care, it was found that more than half of women did not benefit from the following services: size measuring, urinalysis, rubella and toxoplasmosis serology. We also noted a growing concern among women for pregnancy monitoring quality, since 43% were simultaneously monitored by several categories of staff. To improve the quality of prenatal care, we recommend that health professionals complete physical and diagnostic tests, also provide more information about continuity of care during prenatal consultations.